IMPORTANCE OF ENRICHING THE COMPOSITION OF ICE CREAM WITH DRIED FRUIT JUICES - B.N. Sattorova; F.E. Ismoilova (American Journals Publishing, 2023)
The article describes the importance of enriching the composition of ice cream with various dried fruit juices, the methods and research about their benefits for human health.
Keywords: ice cream, apricot juice, natural antibiotic, bacteria, lutein, beta-carotene, pectin, immunity.